Sistem Informasi Akademik Pada SMK Multicomp Depok - Wina Widiati; Refi Indriyani - Universitas Bina Sarana Informatika (SPEED - Sentra Penelitian Engineering dan Edukasi, 2019)
Abstract - Information systems are well designed and built so as to increase productivity, improve service quality so that the need to access information quickly, precisely easily. So that currently the information system is used in various fields, one of which is in the field of education. In academic information systems the use of information technology by presenting educational information in helping manage teaching and learning activities effectively and efficiently. By having a school information system, educational institutions can provide various kinds of information as needed. Depok Multicomp Vocational School requires an information system that supports and provides convenience for principals, teachers and students. For this reason, the writer tries to make a Final Project regarding the academic system about inputting school data and student grades at Multicomp Vocational Schools. The purpose of this study is to produce an academic information system for schools, guardian parents, and students.Keywords: Academic Information System. Abstrak - Sistem informasi dirancang dan dibangun dengan baik agar meningkatkan produktivitas, mengingkatkan kualitas layanan agar kebutuhan untuk mengakses informasi secara cepat, tepat dengan mudah. Sehingga saat ini sistem informasi digunakan di berbagai bidang, salah satunya adalah pada bidang pendidikan. Dalam sistem informasi akademik pemanfaatan teknologi informasinya dengan menyajikan informasi pendidikan dalam membantu mengelola kegiatan belajar mengajar dengan efektif dan efisien. Dengan memiliki sistem informasi sekolah, maka lembaga pendidikan dapat menyajikan berbagai macam informasi sesuai kebutuhan. SMK Multicomp Depok membutuhkan sekali adanya suatu sistem informasi yang mendukung dan memberikan kemudahan bagi kepala sekolah, guru serta siswa. Untuk itu penulis mencoba membuat Tugas Akhir mengenai sistem akademik tentang penginputan data-data sekolah maupun nilai siswa di SMK Multicomp. Tujuan penelitian ini untuk menghasilkan sistem informasi akademik bagi sekolah, orangtua wali, dan siswa. Kata Kunci: Sistem Informasi Akademik.